Lactobacillus salivarius extracellular vesicles enhance gut and liver function in MAFLD - Zhu, Lihui; Huang, Jiwen; Luo, Zhen; Yan, Huaxiang; Wu, Xiao; Liao, Rongrong (Frontiers in Immunology, 2025)
BackgroundMetabolic dysfunction-associated fatty liver disease (MAFLD) is associated with an accumulation of fat in the liver, disruptions in lipid metabolism, and imbalances in the gut microbiome. Extracellular vesicles (EVs) derived from probiotics have emerged as potential mediators of host lipid metabolism effect. The precise mechanisms by which EVs derived from probiotics influence MAFLD are still not fully understood.MethodsWe examined the therapeutic potential of EVs sourced from Lactobacillus salivarius SNK-6 (LsEVs) using a mouse model of MAFLD and fatty acids induced cells.ResultsOral LsEVs administration reduced weight gain, lower liver enzyme levels, and less liver fat in mice. Meanwhile, LsEVs increases the secretion of anti-inflammatory factor IL-4 in mice subjected to a high-fat diet, but inhibited the pro-inflammatory cytokine secretion in lipopolysaccharide induced gut cells. Mechanistically, LsEVs enhance liver cell mitophagy via Beclin-1 and PPAR related pathways. LsEVs also increased tight junction proteins in epithelial cells. Furthermore, LsEVs boost gut bacterial diversity in MAFLD -afflicted mice by promoting beneficial Bacteroidota and suppressing harmful Desulfovibrio.ConclusionsOur research established a foundation for the future use of LsEVs in treating MAFLD and provided novel insights into the mechanisms of lipid metabolism influenced by EVs derived from probiotics in the context of MAFLD.